Encyclopedia of language development - Brooks, Patricia (Patricia J.); Kempe, Vera (Los Angeles : SAGE, 2014)
This encyclopedia covers the breadth of theory and research on language development from birth through adulthood, as well as their practical application. It includes 200 articles that address such topic areas as theories and research tradition; biological perspectives; cognitive perspectives; family, peer, and social influences; bilingualism; special populations and disorders; and more. All articles (signed and authored by key figures in the field) conclude with cross reference links and suggestions for further reading.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Language acquisition -- Encyclopedias